Discovery and functional characterisation of a luqin-type neuropeptide signalling system in a deuterostome - Luis Alfonso Yañez-Guerra; Jérôme Delroisse; Antón Barreiro-Iglesias; Susan E. Slade; James H. Scrivens; Maurice R. Elphick (Scientific Reports, 2018)
Abstract Neuropeptides are diverse and evolutionarily ancient regulators of physiological/behavioural processes in animals. Here we have investigated the evolution and comparative physiology of luqin-type neuropeptide signalling, which has been characterised previously in protostomian invertebrates. Phylogenetic analysis indicates that luqin-type receptors and tachykinin-type receptors are paralogous and probably originated in a common ancestor of the Bilateria. In the deuterostomian lineage, luqin-type signalling has been lost in chordates but interestingly it has been retained in ambulacrarians. Therefore, here we characterised luqin-type signalling for the first time in an ambulacrarian – the starfish Asterias rubens (phylum Echinodermata). A luqin-like neuropeptide with a C-terminal RWamide motif (ArLQ; EEKTRFPKFMRW-NH2) was identified as the ligand for two luqin-type receptors in A. rubens, ArLQR1 and ArLQR2. Furthermore, analysis of the expression of the ArLQ precursor using mRNA in situ hybridisation revealed expression in the nervous system, digestive system and locomotory organs (tube feet) and in vitro pharmacology revealed that ArLQ causes dose-dependent relaxation of tube feet. Accordingly, previous studies have revealed that luqin-type signalling regulates feeding and locomotor activity in protostomes. In conclusion, our phylogenetic analysis combined with characterisation of luqin-type signalling in a deuterostome has provided new insights into neuropeptide evolution and function in the animal kingdom.